Quinoline analogue as a potential inhibitor of SARS-CoV-2 main protease: ADMET prediction, molecular docking and dynamics simulation analysis - Kumar, Praveen; Mahantheshappa, Santhosha Sangapurada; Balasubramaniyan, Sakthivel; Satyanarayan, Nayak Devappa; Achur, Rajeshwara (European Journal of Chemistry, 2023)
The novel coronavirus (COVID-19) has triggered a major human turmoil worldwide by posing challenges regarding infection prevention, disease diagnosis, and treatment. Several drugs including remdesivir (RDV), hydroxychloroquine (HCQ), and others are being used to treat COVID-19, although these are not specifically proven drugs. Thus, it is very critical to understand COVID-19 drug targets and their interactions with candidate drugs. Here, we attempted in silico screening of ten quinoline analogs (Q1-Q10) against the five main proteases of SARS-CoV-2 by docking and dynamics analysis. The prediction of the ADMET profile showed that the best docked quinolines are safe and possess drug-like properties. The molecular interaction and binding affinity of these small molecules were determined with respect to the five protease (Mpro) targets of SARS-CoV-2 (PDB ID: 6LU7, 6W63, 6M03, 6Y84 and 6YB7). The study indicated that the quinoline ligands Q4, Q5, Q6, Q7, Q8, Q9, and Q10as probable inhibitors against SARS-CoV-2 Mpro and showed favorable binding interaction with the amino acid Glu166 of 6Y84, 6LU7and 6M03. Furthermore, Q9 has a highly significant docking score and binding affinity with all fiveCOVID-19 receptors having a minimum of two H-bonds, which is remarkable compared to HCQ, RDV, and other quinolines. The dynamics simulation analysis of this potent drug candidate Q9 with 6LU7 indicated high stability of the complex. In conclusion, our findings indicate that all of these quinolines in general possess good binding affinity and Q9 can serve as a good quinoline scaffold for the design of new antiviral agents to target the active site of SARS-CoV-2 MPro.